Kebermaknaan Hidup Pemimpin Organisasi Mahasiswa Yang Mengalami GAP Year - Sugiharto, Bagas; Purbaning Tyas, Prias Hayu (Universitas Sanata Dharma, 2025)
This research aims to (1) identify the various ways to interpret the dynamics of personal development for organizational leaders who have experienced a Gap Year, (2) understand the different perspectives of organizational leaders who have experienced a Gap Year regarding suffering in finding meaning in life, (3) determine the various influences felt by organizational leaders who have experienced a Gap Year as a result of their search for meaning in life, and (4) identify the various obstacles in the process of finding meaning in life within each dynamic of the organization led by organizational leaders who have experienced a Gap Year. This research employs a qualitative method with a phenomenological approach. Data collection was conducted through observation and interviews with two research subjects who are organizational leaders who experienced a Gap Year due to working before attending university. The research results indicate that both subjects were able to find meaning in life as organizational leaders who had experienced a Gap Year. The data obtained shows that both (1) subjects had their own ways of finding meaning in their lives. (2) Although some events within the organization evoked negative emotions such as anger and disappointment, both subjects tried to accept and be grateful for them as part of the journey. (3) Age differences with their members also influenced the emergence of problems that hindered the discovery of meaning in life, although both subjects were ultimately able to overcome them. (4) Various problems present in the organization served as a form of maturation and supported self-actualization as organizational leaders.